2011
DOI: 10.1152/ajpheart.00084.2011
|View full text |Cite
|
Sign up to set email alerts
|

Uridine adenosine tetraphosphate-induced contraction is increased in renal but not pulmonary arteries from DOCA-salt hypertensive rats

Abstract: Matsumoto T, Tostes RC, Webb RC. Uridine adenosine tetraphosphate-induced contraction is increased in renal but not pulmonary arteries from DOCA-salt hypertensive rats. Am J Physiol Heart Circ Physiol 301: H409 -H417, 2011. First published May 6, 2011 doi:10.1152/ajpheart.00084.2011.-Uridine adenosine tetraphosphate (Up 4A) was reported as a novel endothelium-derived contracting factor. Up 4A contains both purine and pyrimidine moieties, which activate purinergic (P2)X and P2Y receptors. However, alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 57 publications
(113 reference statements)
0
47
0
Order By: Relevance
“…148 Burnstock and Ralevic Up 4 A was enhanced (Matsumoto et al, 2011). P2Y 2 receptor gene haplotypes are associated with essential hypertension in Japanese men (Wang et al, 2010b).…”
Section: A Hypertensionmentioning
confidence: 96%
See 1 more Smart Citation
“…148 Burnstock and Ralevic Up 4 A was enhanced (Matsumoto et al, 2011). P2Y 2 receptor gene haplotypes are associated with essential hypertension in Japanese men (Wang et al, 2010b).…”
Section: A Hypertensionmentioning
confidence: 96%
“…The concentration of Up 4 A, a dinucleotide claimed to be an endothelium-dependent vasoconstrictor, is increased in plasma of juvenile hypertensives and may contribute to the early development of primary hypertension (Jankowski et al, 2007). Up 4 A-induced contractions, mediated by P2X 1 , P2Y 2 , or P2Y 4 receptors, were increased in renal, basilar, and femoral, but not in pulmonary arteries from DOCA-salt hypertensive rats (Matsumoto et al, 2011(Matsumoto et al, , 2012. The authors attributed this to enhanced P2Y signaling in the renal artery, because contractions mediated by P2Y 2 , P2Y 2/4 , and P2Y 6 receptor agonists were also enhanced; there was no change in renal artery protein expression of P2Y 2 , P2Y 4 , and P2Y 6 receptors in DOCAsalt hypertension, but ERK activation stimulated by (Inscho, 2009) and human subcutaneous veins (Lind et al, 1997).…”
Section: A Hypertensionmentioning
confidence: 96%
“…Increased activation of ERK1/2 in various arteries contributes to augmented vascular contraction and subsequent cardiovascular disease pathologies [30,29]. In addition, we recently demonstrated that the activation of ERK1/2 plays a role in the contractile phenotype modulation of VSMCs [8].…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, other factors such as endothelium-derived hyperpolarizing factor (EDHF) and cyclooxygenase (COX)-mediated substances (prostanoids) are important in the regulation of vascular tone. [19][20][21]24) Indeed, several studies have suggested that 1) vascular responses to extracellular nucleotides/nucleosides are altered in the vasculature of hypertensive individuals, 11,16,29,30) and 2) these endogenous ligand-induced responses are mediated by arterial endothelium-derived factors under various conditions. 13,14,30,31) However, very few studies have investigated the vasorelaxant activity of ATP/ADP/adenosine along with the modulative effects of NO and COX-derived substances on the same arteries in hypertensive individuals.…”
Section: 18)mentioning
confidence: 99%
“…Several studies have suggested that the expression and signaling responses of these receptors is altered under disease conditions. 4,11,[13][14][15][16][17] Moreover, these receptors can mediate a variety of responses to several nucleotides, resulting in the existence of multiple receptors with overlapping ligand preferences. …”
mentioning
confidence: 99%